Biocompatible macrocyclization between cysteine and 2-cyanopyridine generates stable peptide inhibitors - Nitsche, Christoph (2020)
Peptides featuring an N-terminal cysteine residue and the unnatural amino acid 3-(2-cyano-4-pyridyl)alanine (Cpa) cyclize spontaneously in aqueous solution at neutral pH. Cpa is readily available and easily introduced into peptides using standard solid-phase peptide synthesis. The reaction is orthogonal to all proteinogenic amino acids, including cysteine residues that are not at the N-terminus. A substrate peptide of the Zika virus NS2B-NS3 protease cyclized in this way produced an inhibitor of high affinity and proteolytic stability.